Fluctuating paraplegia secondary to spinal epidural lipomatosis: a case report - El Ayssami, Malak; Adem, Carmen; Attieh, Christian; Khoury, Mounir (Frontiers in Surgery, 2025)
Spinal epidural lipomatosis (SEL) is a rare condition characterized by excessive growth of adipose tissue in the epidural space, leading to spinal cord or nerve root compression. We present a case of a 37-year-old obese male who developed fluctuating paraplegia secondary to SEL. The patient initially presented with ascending weakness, which rapidly progressed to paraplegia, accompanied by sensory deficits and urinary incontinence. MRI revealed SEL with associated spinal cord compression. Although initially planned for decompressive surgery, the patient showed partial recovery, delaying the procedure. After laminectomy and excision of the lipomatosis, the patient demonstrated significant motor improvement, although mild sensory deficits persisted. Histopathological analysis confirmed the presence of adipocytes. This case highlights the importance of recognizing SEL, especially in patients with fluctuating neurological symptoms. Treatment strategies include weight management and surgical decompression, with a favorable prognosis for those undergoing timely intervention. Early diagnosis through MRI and appropriate management is key to improving outcomes.